Will Healthcare Workers Accept a COVID-19 Vaccine When It Becomes Available? A Cross-Sectional Study in China - Sun, Yufang; Chen, Xiaohong; Cao, Min; Xiang, Tao; Zhang, Jimei; Wang, Ping; Dai, Hang (Frontiers in Public Health, 2021)
Objective: The Coronavirus disease 2019 (COVID-19) vaccine is currently available. This timely survey was conducted to provide insight into on the willingness of healthcare workers （HCWs）to receive the vaccine and  determine the influencing factors. Methods: This was a cross-sectional online survey.An online questionnaire was provided to all participants and they were asked if they would accept a free vaccine. The questionnaire gathered general demographic information, and included the General Health Questionnaire (GHQ-12); Myers-Briggs Type Indicator questionnaire (MBTI); Depression, Anxiety, and Stress Scales (DASS-21); and the 12-item Short Form Health Survey (SF-12). The data were collected automatically and electronically. Univariate analysis was done between all the variables and our dependent variable.Multivariable logistic regression models were employed to examine and identify the associations between the acceptance of the COVID-19 vaccine with the associated variables. Results: We collected 505 complete answers. The participants included 269 nurses (53.27%), 206 clinicians (40.79%), 15 administrative staff (2.97%), and 15 other staff (2.97%). Of these, 76.63% declared they would accept the vaccine. The major barriers were concerns about safety, effectiveness, and the rapid mutation in the virus. Moreover, four factors were significantly associated with the willingness to receive the vaccine : (a) “understanding of the vaccine” (odds ratio (OR):2.322; 95% confidence interval [CI]: 1.355 to 3.979); (b) “worried about experiencing COVID-19” (OR 1.987; 95% CI: 1.197 to 3.298); (c) “flu vaccination in 2020” (OR 4.730; 95% CI: 2.285 to 9.794); and (d) “living with elderly individuals” (OR 1.928; 95% CI: 1.074 to 3.462). Conclusions: During the vaccination period, there was still hesitation in receiving the vaccine..The results will provide a rationale for the design of future vaccination campaigns and education efforts concerning the vaccine.